PENGUKURAN TINGKAT KESEHATAN PT BANK RAKYAT INDONESIA (PERSERO) TBK DENGAN METODE CAMEL - Wawan Kurniawan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
Analyze the health level of Bank BRI in Indonesia with camel method. The research methodology used is qualitative descriptive research with case study approach. Which using this type of time series data from secondary data from the Indonesia Stock Exchange. Mechanical sampling using purposive sampling method with annual data from 2011 -2015. Data were analyzed using methods camel in measuring the health level of a bank. The results of this study indicate the ratio of capital represented BRI Bank capital adequacy ratio has a value of CAR above the provisions of Bank Indonesia. The ratio of assets which represented the quality of earning assets Bank BRI has KAP value ratio above the provisions of Bank Indonesia. Management ratio represented the net profit margin of Bank BRI has NPM value ratio above the provisions of Bank Indonesia. Earnings ratios are represented as return on assets and net interest margin of the Bank BRI has a value of ROA and NIM above the provisions of Bank Indonesia. While earnings ratio of other operating expenses operating income represented Bank BRI has BOPO value ratio above the provisions of Bank Indonesia. Liquidity ratio as represented current ratio of Bank BRI has a CR value ratio above Bank Indonesia. While other liquidity ratio as represented loan to deposit ratio and loan to assets ratio has a value of Bank BRI LAR LDR and above the provisions of Bank Indonesia. The health level of banks which is calculated based on the CAMEL ratio showed BRI is a bank that has a good health level.